The extended therapy room coming from an authentic place... : a phenomenological-hermeneutic study of my experiences as a psychotherapist in the Extended Therapy Room - Håkansson, Carina (2014)
Many times over the years as I've worked in the Extended Therapy Room in situations with others I have asked myself what in the work we do touches and affects, and what part I as a psychotherapist play in that. In what way do I and my way of being-in-the-world contribute to what unfolds in the therapeutic meeting? Is it even possible to arrive at a conclusion through research or should the question be put some other way? A world in movement and an existence without generally accepted answers on one side, and the need to hold onto something on the other. This is the way life is for us human beings, and also the way it is in the therapeutic room. So how do we relate to this both- and? What kind of knowledge can you generalize about and how do you pass on your own experience so that someone else can use it? How do you create meaning from what I call ordinary life in therapeutic work? Over the years of working together with both family homes that provide an ordinary context and psychotherapists and other professional helpers I have experienced our clients become "something else" than the label they were given before we began working together. I've also experienced how those of us involved in the process; the client's family, family home, therapist and supervisor have been affected by it. I have experienced a noticeable difference that has left mark on my work and perspective on psychotherapy. My years of experience have generated questions about the essence of the therapeutic meeting and how to bring to life and include the therapist, both as a human being and a professional, in practice and as part of the description of what happens. These questions and years of practice and studies have together led to the formulation of the research question: What is the most important in my experience as a psychotherapist in the Extended Therapy Room? This dissertation describes an experience-based knowledge that has developed from practice built on each and everyones presence and participation. This practice combines ordinary life with therapeutic knowledge and is not primarily about theoretic perspectives and therapeutic techniques, but the meeting between people and how these meetings in different ways make an impact, not only on the one here called client, but on all of us included in the shared commitment and the organization in its whole. The research material is made up of fourteen stories where I'm part of the events that take place, mainly as a psychotherapist but in one story I'm a social worker and in another I'm a child. The investigation is based on a phenomenological-hermeneutic method which was developed in order to understand what emerges from one's own lived experience (Lindseth and Norberg, 2004). By moving as a researcher between the naїve reading and the structural analysis within the framework of the hermeneutic circle seven main themes have emerged and together they constitute the results of the research: Being present, participating, being part of an ordinary context, meeting, taking personal responsibility, communicating and enabling. These main themes are described and illustrated in the Critical reflection section. In the section Theoretic Reflection and Discussion these main themes are reviewed in depth and discussed in relationship to other research and practice, mainly in the field of psychotherapy and philosophy, but also in relation to art and physics. The dissertation concludes with a Method reflection that describes the method's effect on the research and the researcher's approach. The question wheather it is possible to arrive at a conclusion about the importance of the therapists own lived experience through research was raised in the beginning, and as this project now has come to an end it has become clear that it is possible. Not only possible, but also important, as it is important how to ask questions and how to act. Through this research project it has become clear how traditional psychiatry and psychotherapy far too much focus on the one here called client and by doing so create a context which rather exclude than include, especially by the use of psychiatric diagnosis and descriptions of the other. The most important in my experience as a psychotherapist in the Extended Therapy Room doesn't primarily concern different therapeutic methods or specific therapeutic doctrines or schools, but rather the importance of a personal stance and to utilize lived experience in an organisation that enables people to be authentic and include themselves in vital meetings.